Trends in Rainfall and Economic Growth in Africa: A Neglected Cause of the Growth Tragedy - Salvador Barrios Cobos; Luisito Bertinelli; Eric Strobl (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
We examine the role of trends in rainfall in the poor growth performance of sub-Saharan African nations relative to other developing countries. To do so we use a new crosscountry panel climatic data set in an empirical economic growth framework. Our results show that rainfall has been a significant determinant of poor economic growth for Africa, but not for other developing countries. Depending on the benchmark measure of potential rainfall, we estimate that the direct impact under the scenario of no decline in rainfall would have resulted in a reduction of between around 15 and 40 per cent of today's gap in African GDP per capita relative to the rest of the developing world.
Keywords: 330